(untitled) (Literary Voice, 2023)
Often literary analyses include a discussion of figures of speech, characters and thematic issues from a theoretical perspective but issues of language and gender have received little attention from literary commentators. Drawing on the writings of Robin Lakoff and Deborah Tannen, two celebrated feminist linguists, this paper seeks to highlight how concepts from the area of language and gender can provide deeper insights into literary texts and the interaction of characters. To this effect, the present study examines three aspects – conversational style, the polysemous meanings of linguistic strategies and the use of sexist language – explicating these in Chitra Banerjee Divakaruni’s The Palace of Illusions.